ANALISIS KEPUTUSAN PENDANAAN PERUSAHAAN: PENGUJIAN EMPIRIK PECKING ORDER THEORY DAN BALANCE THEORY - Sujoko, Sujoko (Journal of Innovation in Business and Economics, 2010)
This study addresses the spesific issue of how firm actually select between   equity or debt.  The coefficient of model are estimated using multivariate logistic regression. This study throws light on a number of interesting issues. Firstly, it demontrates that companies are heavely influenced by market condition and the past history of security price in choosing between equity and debt. Secondly, it provides empirical evidene that company appears to be consistent with the pecking order theory. Finally, the evidence in regard to balancing theory is less clear. It result are interesting, since the higher of business risk and volatility level, firms are more likely using the higher debt. It is not consistent with balance theory.